Social protection systems and economic benefits during the 2008-2014 period of the Great Economic Recession. A reflection from the case of Andalusia - Carrasco Salas, Manuel Jesús; Borrego Alés, Yolanda; Vázquez Aguado, Octavio (IJERI: International Journal of Educational Research and Innovation, 2020)
Numerous studies have shown the impact of the economic crisis on social protection systems, especially in community or grass-roots social services. The efforts made by the Autonomous Communities and local authorities to finance these protection systems, and the consequent effect that this has had on social expenditure items, are two constants that appear in research on the subject. In this work, the focus has been on the economic benefits of community social services in Andalusia, to relate them to other economic benefits of other social protection systems and to observe the behaviour of all of them during the period of economic crisis. The increase in recipients and social expenditure on these economic benefits contradicts what is happening in absolute terms and, Clearly, it highlights a system that has had to go out and address situations of familial economic deprivation at the time of the Great Economic Depression.